A case study of 10 years groundwater radon monitoring along the eastern margin of the Tibetan Plateau and in its adjacent regions: Implications for earthquake surveillance. (August 2021) - Zhao, Yuanxin; Liu, Zhaofei; Li, Ying; Hu, Le; Chen, Zhi; Sun, Fengxia; Lu, Chang
Abstract: The eastern margin of the Tibetan Plateau has been characterized by frequent disastrous earthquakes, which has induced changes in groundwater such as variations in isotopes, ions, and dissolved gases. In this study, the fluctuation of groundwater radon recorded at six different monitoring stations from 2009 to 2018 was analyzed. With the statistical approach (the residual signal processing technique and the Hurst exponent estimates), groundwater radon variations caused by seismic events were unraveled, reflecting regional stress status changes. The results of this study indicated that (1) groundwater radon exhibits distinct differences between the eastern margin of the Sichuan-Yunnan Block and the South China Block; (2) the precursory anomalies of groundwater radon are principally categorized into three types: positive, negative, and dual behaviors; (3) the relatively low level of the groundwater radon results from the underlying rock masses resisting the compressional stress and the locking on the Xianshuihe fault, the Anninghe fault, and the Zemuhe fault. Additionally, the seismic response zone of each monitoring station was delineated using historical seismic precursors. Highlights: Groundwater radon has a strong correlation with geological settings. Precursors of radon include three types: positive, negative, and dual behaviors. The seismic response zone is helpful for regional earthquake surveillance.